Development of Multi-Developer Housing Marketing Information System Using Rational Unified Process Method - Kurniadi, Dede; Setiawan, Ridwan; Adiwangsa, Alfian Akmal; Lindayani, Lindayani (Politeknik Ganesha Medan, 2023)
Rumah Garut is a company engaged in selling property to several housing developers. In the housing marketing process, it is still carried out offline, where the developer carries out the registration process with marketing company, then makes brochures and markets them at exhibitions. This method is considered inappropriate, given the large number of housing units registered by the developer, as it would delay the marketing or sale of the house. This research aims to develop an online marketing information system that can be carried out with multiple developers so that each developer can manage and inform their housing effectively and efficiently. The system design method is the Rational Unified Process (RUP), which consists of the stages of inception, elaboration, construction, and transition. The results of this study are in the form of a multi-developer housing marketing information system that can assist housing developers in managing and users in accessing housing information and ordering online. Meanwhile, based on the results of black box testing, it shows that the features developed are in accordance with the specified system functional scenarios, and testing the results of beta testing produces a score of 93.7%, which means that the housing marketing system meets user needs.